Nanoparticle-loaded protein-polymer nanodroplets for improved stability and conversion efficiency in ultrasound imaging and drug delivery - Lee, J; Stride, E; Carugo, D; Victor, M; Crake, C; Owen, J; Seth, A; Coussios, C (University of Oxford, 2015)
These data were created on 15th July of 2015 for the paper to be published in Advanced Materials. We have developed a new formulation of volatile nanodroplets, stabilised by a protein and polymer coating. The nanodroplets are prepared from hydrophobic perfluoropentane (PFP) and coated with human serum albumin and polyethylene glycol modified N-hydrosuccinimide conjugated in dichloromethane using an oil-in-water emulsification method. The resulting nanodroplets have an average diameter of 344 nm and are stable at 37oC for several days. These properties offer advantages both for storage of the droplets and their ability to extravasate and permeate target tissue as compared with microbubble agents. Upon exposure to ultrasound the nanodroplets undergo a phase change, generating microbubbles. The efficiency of this process was increased by a factor of 2.8 when iron oxide nanocrystals were added to the PFP. In addition, hydrophobic drugs can be incorporated into the droplet core and the release characteristics of an anti-cancer drug, paclitaxel, were studied. The rate of drug release was found to increase by 70.7 % compared to a control formulation without PFP upon exposure to ultrasound for 180 seconds. Finally the effect of the nanodroplets on breast cancer cells was compared with that of the control formulation, and it was found that the droplets showed 38%p enhanced cytotoxicity than that of free drug.